Korelasi Antar Beberapa Sifat Sensorik Jubedhe - Achmad Subagio (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1993)
Jubedhe were prepared from different proportions of raw material analyzed for the sensory characteristics.The result indicated that aroma was the greatest factor effecting the jubedhe acceptability, while texture and color determined the jubedhe acceptability small sweetness did not influence the jubedhe acceptability significantly. Aroma together with texture and colour given influence to the jubedhe acceptability about 67%.